Na+-H+ exchanger inhibition : A new antihypertrophic tool - Cingolani, Horacio Eugenio (2002)
Cardiac hypertrophy (CH) is a major risk factor for cardiac death and commonly precedes the development of heart failure (HF). This is motivating the search for novel pharmacological strategies to prevent the development and/or regress CH. Although the signaling pathways leading to myocardial hypertrophy are complex, one important set of pathways involves the mitogen-activated protein kinases (MAPKs). MAPKs phosphorylate numerous substrates, including nuclear transcription factors that activate the expression of different genes. The Na+-H+ exchanger (NHE) is a common downstream effector of this cascade and has been implicated in different models of hypertrophy, such as “hypertensive” myocardium, aortic constrictioninduced hypertrophy, and postinfarction myocardial hypertrophy. Interestingly, stretch-induced hypertrophy of cultured neonatal cardiomyocytes is also accompanied by an increase in MAPK activity and NHE activation. Furthermore, stretch-induced MAPK stimulation is partially prevented by inhibition of NHE activity.